Al-Qur’an dan Lahirnya Sains Teistik - Mohammad Muslih (Universitas Darussalam Gontor, 2016)
The discourse of integration of religion and science could enrich research of al-Qur’an study. As a principal source of Islam, al-Qur’an also becomes object research of the philosophy of science study, especially related to the development of science-based on religion. Within the framework of the philosophy of science, this article presents a study on the possibility to develop science-based on alQur’an, which is called “theistic science”. Although the efforts to find root of science on al-Qur’an develop so far, or to interpret al-Qur’an by utilizing the result of science research, in the framework of the philosophy of science, but it is not surely called a “science theistic”, even so perhaps it is not science, but it may be merely indeed not scientific. There is a pattern of development of science which is based on religion, but it is really scientific, which consists of three layers of philosophical basis, they are theoretical framework, scientific paradigm, and theological basis. By following this pattern carefully, the development of science not only can avoid the pattern of pseudoscience, but it will create science with high scientific value, but it is still within the framework of al-Qur’an. It is organized based on the embryonal concept from al-Qur’an. However, this pattern is a collective project, systemic, and cultural in the form of a grand project.